An enhanced test case generation technique using activity diagram for system testing - Yudaya, Nansukusa (2013)
Software Testing, a process comprised of test case generation, execution and evaluation is one of the imperative phases of the development life cycle, with its cost approximated to about 50% of the overall development cost. Researchers have automated it using models with utmost focus put on Unified Modeling Language (UML) as the up to date de facto standard utilized in software modeling. Its diagrams include both behavioral and structural. This work has generated system tests (black box) early in the development lifecycle hence the use of behavioral models, activity diagrams in particular as they are one of the earliest and simplest analysis models to be created with sufficient testing information. Also, as a way of reducing test case generation effort and time, an existing technique that supposedly involved more effort and time has been focused on in this work. It has been enhanced by reducing the key steps involved through eliminating intermediate models as a way of reducing effort and time involved in the test case formation process. The enhanced technique has been applied on the same case study as in the original technique, producing four test cases in 115 milliseconds with more ease compared to the original technique that produced five test cases in 160 milliseconds with relatively more effort. It has further been compared against another already existing model based technique (based on sequence diagrams) and also one integrated with a model based tool using both general criteria and those specific to the research problem (TCG effort and time), as a way of further confirming its applicability.